Legal Review of The Implications of The Principle of Dominus Litis for Prosecutors with Restorative Justice Efforts in Criminal Justice Processes (Research Study at The West Halmahera District Attorney's Office) - Soeroso, Raka Aprizki; Gunarto, Gunarto (Jurnal Hukum Khaira Ummah, 2025)
Currently, the legal system in Indonesia is experiencing development. This development emphasizes the orientation of criminal case resolution which was initially based on the retributive paradigm that provides retribution for crimes committed by the perpetrator towards a new approach model, namely "Restorative Justice". In order to adapt to existing developments and achieve legal and national goals, the Prosecutor has issued a legal product regarding restorative justice in handling criminal cases at the prosecution stage (the authority of the Prosecutor as Dominus Litis). This study aims to determine and analyze (1) a philosophical legal review of the concept of restorative justice in the Indonesian criminal justice system, (2) the relationship between the principle of dominus litis of the prosecutor and restorative justice efforts in the criminal justice process, and (3) the problem of the function of dominus litis of the prosecutor in applying the concept of restorative justice in the criminal justice process. The approach method used in this study is sociological juridical. The specifications of this study are descriptive analytical. The data sources used are primary data and secondary data. Primary data is data obtained directly from the field or from the first source and has not been processed by other parties. While secondary data is obtained from library research consisting of primary legal materials, secondary legal materials and tertiary legal materials. The results of the research and discussion can be concluded: (1) Restorative justice philosophically has a foundation contained in the fourth and fifth principles of Pancasila, which have the essence of meaning towards the values of deliberation and justice. Pancasila as the ideology and outlook on life of the Indonesian nation is used as a guide for all activities in life in every field. (2) This new justice model is then formulated in the form of technical instructions that can be used as a reference in handling cases with a restorative justice approach. On July 21, 2020, the Indonesian Attorney General issued Regulation of the Attorney General of the Republic of Indonesia Number: 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice. Restorative justice is one of the efforts that can be made by the Prosecutor's Office in functionalizing the principle of Dominus Litis. (3) The regulation regarding the principle of dominus litis through restorative justice in the Criminal Procedure Code (KUHAP) in Indonesia is still unclear. Restorative justice is a legal approach that emphasizes reconciliation between perpetrators, victims, and the community, and has not been regulated in detail in the current Criminal Procedure Code.